Socioenvironmental changes in two traditional food species of the Cree First Nation of subarctic James Bay - Royer, Marie-Jeanne; Herrmann, Thora (Cahiers de géographie du Québec)

(untitled) (Département de géographie de l’Université Laval, 2011)
AbstractSocioenvironmental changes in Canada’s northern regions are likely to have wide-ranging implications for the health of its residents. Aboriginal communities are among the first to face the direct impacts of changes, as their lifestyles tend to be more closely tied to and reliant upon the natural environment. Based on field research, this paper documents observations of socio-environmental changes made by members of the Cree Trappers Association (CTA) of the Cree of Eeyou Istchee (the traditional homeland of the Cree located in the eastern James Bay area). It also analyses their impact on hunting behaviour and consumption levels associated with two traditional food species – the Canada Goose and the woodland caribou. CTA members are witnessing changes in animal behaviour and the migration patterns of species. These in turn are affecting the consumption of traditional food, causing dietary changes at the society level, and, ultimately, impacting on human health and overall well-being.